Identification of Plant Semiochemicals and Characterization of New Olfactory Sensory Neuron Types in a Polyphagous Pest Moth, Spodoptera littoralis. (5th September 2014) - Binyameen, Muhammad; Anderson, Peter; Ignell, Rickard; Birgersson, Göran; Razaq, Muhammad; Shad, Sarfraz A.; Hansson, Bill S.; Schlyter, Fredrik
Abstract : Phytophagous insects use blends of volatiles released from plants to select hosts for feeding and oviposition. To behaviorally analyze complex blends, we need efficient and selective methods for elucidating neuron types, their ligands, and specificity. Gas chromatography-combined single sensillum recordings (GC-SSRs) from antennal olfactory sensilla of female moth, Spodoptera littoralis revealed 38 physiologically active peaks in the headspace volatile blends from both larvae-damaged cotton plants and lilac flowers. Using GC-combined mass spectrometry, 9 new physiologically active compounds were identified from damaged cotton and 11 from lilac compared with earlier electrophysiological studies using antennae of female S. littoralis . We characterized 14 novel classes of olfactory sensory neurons (OSNs). Among these, we found the first 2 ligands for a frequent type of short trichoid sensillum, for which no ligands were identified earlier. By using GC-SSR, a substantial increase in functional classes of OSNs and active compounds, 40% and 34% more, respectively, compared with recent studies using GC-electroantennogram or SSR using single compounds was detected. Compared with the estimated number of corresponding antennal olfactory receptors, the OSN classes now correspond to 83% of a likely maximum. The many specialist OSNs observed may facilitate behavioral confirmation of key plant volatiles in blends.